Prize winning white Leghorns (1945)
Photo caption reads: 'Eggs and poultry are produced on the college farm. The plant has facilities for 4,000 laying and breeding hens, and broods about 12,000 chicks each season. In addition there is a modern poultry dressing plant.' Photo depicts four Cal Poly students with Cal Poly's student-owned entries in the annual national contest, winning the three-year award for top production in 1945.